Structure and in vitro transcription of a glycine tRNA gene from Bombyx mori. - Fournier, A (1984)
We report the sequences of a Bombyx mori tRNA1Gly gene, its flanking regions, and its in vitro transcription products. The 5' flanking DNA contains the sequences TATAC, TATTTT and TTC located 30, 18 and 4 nucleotides, respectively, in front of the transcription initiation site. These resemble, in both position and composition, sequences preceding other RNA polymerase III genes of B. mori. A deletion mutant retaining these conserved sequences and an additional 8 bp of flanking DNA is transcribed better than the wild-type gene in cell-free extracts from Xenopus laevis and B. mori. A mutant lacking the conserved sequences is expressed in the frog extract, but is inactive in the homologous system.